Prolonged Disease Course of COVID-19 in a Patient with CTLA-4 Haploinsufficiency - T. W. Hoffman; H. L. Leavis; B. M. Smits; L. T. van der Veken; D. A. van Kessel (Case Reports in Immunology)
Patients with primary immunodeficiencies are especially vulnerable to developing severe coronavirus disease 2019 (COVID-19) after infection with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Cytotoxic T lymphocyte antigen-4 (CTLA-4) is an important regulator of immune responses, and patients who suffer from CTLA4 haploinsufficiency have hyperactivation of effector T cells and infiltration of various organs. Overexpression of CTLA4 has been associated with a more severe disease course in patients with COVID-19, but there have only been a few reports on the disease course of COVID-19 in patients with CTLA4 haploinsufficiency. We report on a 33-year-old female with a history of immune thrombocytopenia, autoimmune haemolytic anaemia, granulomatous-lymphocytic interstitial lung disease, and common variable immunodeficiency who developed COVID-19. She was admitted and discharged from the hospital several times in the months thereafter and remained symptomatic and had a positive SARS-CoV-2 PCR for up to 137 days after the first symptoms. No SARS-CoV-2 antibodies were identified in the patients’ serum. The disease was finally controlled after repeated infusions of convalescent plasma and treatment of concurrent bacterial and fungal infections. Genetic analysis revealed a likely pathogenic variant in CTLA4, and CTLA4 expression on regulatory T-cells was low. This case illustrates that patients with primary immunodeficiencies who have a protracted disease course of COVID-19 could benefit from convalescent plasma therapy.